Maternal depression during the perinatal period: the role of Sensory Processing Sensitivity and social support and its impact on infants’ negative affect - Sperati, Alessandra; Passaquindici, Ilenia; Persico, Melba Emilia; Di Matteo, Cinzia; Fasolo, Mirco; Lionetti, Francesca; Spinelli, Maria (Frontiers in Psychology, 2025)
BackgroundThe perinatal period is marked by significant physiological and psychological changes, making it a challenging time for many women. While some women are more vulnerable to depression during this period, research on perinatal depression trajectories and contributing factors remains mixed. This longitudinal study investigated how maternal depression changes during the perinatal period in a non-clinical sample, exploring the roles of individual factors, such as Sensory Processing Sensitivity (SPS), and contextual factors, such as global partner support. Based on the prenatal programming hypothesis, we also examined the role of prenatal depression on infants’ negative affect temperament as an early marker of emotional adjustment.MethodEighty-eight mothers (M = 35.03 years, SD = 4.92) completed online questionnaires during pregnancy, at 3, 6, and 9 months post-partum. Depression was assessed using the Edinburgh Postnatal Depression Scale, partner support was measured with an ad-hoc scale. SPS was reported during pregnancy using the Highly Sensitive Person Scale. At 3 months post-partum, infants’ negative affect (M = 3.07 months, SD = 0.26) was measured using the Infant Behavior Questionnaire. Latent growth analyses and multivariate regression models were used to analyze the data.ResultsDepression showed a significant linear decrease, with higher symptoms between pregnancy and 3 months postpartum, although overall levels were low and consistent with non-clinical populations. High SPS predicted greater depressive symptoms across all time points. Pregnancy partner support was associated with lower depressive symptoms during pregnancy (β = −0.42, p < 0.01) and at 6 months postpartum (β = −0.32, p = 0.03). Prenatal depression significantly predicted infants’ negative affect (β = 0.34, p = 0.03), particularly the fear temperament subscale (β = 0.46, p = 0.001), accounting for 22% of its variance.DiscussionThe findings clarify that a decline in mood is common in non-clinical populations during the perinatal period, with mothers high in sensitivity and mothers with lower partner support being more vulnerable to experience negative feelings. Moreover, prenatal maternal depression acts as a prenatal stressor, increasing infants’ reactivity to stimuli, as reflected in heightened fear. Implications for tailored parenting programs are discussed.